2009
DOI: 10.1128/cvi.00435-08
|View full text |Cite
|
Sign up to set email alerts
|

Mucosal Adjuvanticity of a Shigella Invasin Complex with DNA-Based Vaccines

Abstract: Protection against many infectious diseases may require the induction of cell-mediated and mucosal immunity. Immunization with plasmid DNA-based vaccines has successfully induced cell-mediated immune responses in small animals but is less potent in humans. Therefore, several methods are under investigation to augment DNA vaccine immunogenicity. In the current study, a mucosal adjuvant consisting of an invasin protein-lipopolysaccharide complex (Invaplex) isolated from Shigella spp. was evaluated as an adjuvant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…Adjuvanticity of S. flexneri 2a Invaplex AR . In addition to inducing Shigella-specific immune responses, Invaplex NAT also functions as an adjuvant, capable of enhancing the magnitude of the immune response directed to coadministered protein antigens (26) or antigens encoded on plasmid DNA (27). To determine if adjuvanticity was retained with Invaplex AR , groups of mice were intranasally immunized with either ovalbumin (OVA) alone or in combination with S. flexneri 2a Invaplex NAT , Invaplex AR , or cholera toxin (CT), a known mucosal adjuvant.…”
Section: Figmentioning
confidence: 99%
See 2 more Smart Citations
“…Adjuvanticity of S. flexneri 2a Invaplex AR . In addition to inducing Shigella-specific immune responses, Invaplex NAT also functions as an adjuvant, capable of enhancing the magnitude of the immune response directed to coadministered protein antigens (26) or antigens encoded on plasmid DNA (27). To determine if adjuvanticity was retained with Invaplex AR , groups of mice were intranasally immunized with either ovalbumin (OVA) alone or in combination with S. flexneri 2a Invaplex NAT , Invaplex AR , or cholera toxin (CT), a known mucosal adjuvant.…”
Section: Figmentioning
confidence: 99%
“…Studies conducted with protein antigens (ovalbumin, protective antigen from Bacillus anthracis, CFA/I antigen from enterotoxigenic E. coli, and FlaA from Campylobacter jejuni) have demonstrated that Invaplex NAT increases the magnitude of the humoral and cellular immune response directed to the coadministered antigen (26). Furthermore, Invaplex NAT also enhanced the immune response directed to vaccine antigens encoded on DNA plasmids (27). The adjuvanticity of Invaplex has been partially attributed to its inherent ability to induce cellular uptake of coadministered antigens as well as providing the necessary Toll-like receptor 4 (TLR-4) agonist that stimulates robust immune responses.…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, intracellular bacteria can be a costeffective delivery method; these live-attenuated bacterial delivery vaccines have proven efficacious against infectious diseases and cancer. Some examples include: Salmonella typhi [82], Listeria monocytogenes [83,84], Shigella flexneri [85], Yersinia enterocolitica [86] and invasive E. coli [87]. Finally, nanotechnology that is complexed with DNA is currently being explored for the facilitation of receptor-mediated vaccine internalization.…”
Section: Delivery Option: the Key For Success?mentioning
confidence: 99%
“…Cited results indicate that this complex was safe and immunogenic in humans. 259 What is of wider interest is that Invaplex has been demonstrated to be an effective mucosal adjuvant when co-administered intranasally with DNA-encoded antigens. 259 Further studies are clearly needed to assess the potential of the complex as an effective, non-toxic mucosal adjuvant.…”
Section: Vaginal and Rectal Delivery Systemsmentioning
confidence: 99%